2011
DOI: 10.1080/09585176.2011.627206
|View full text |Cite
|
Sign up to set email alerts
|

The teaching and learning of pupils in low‐attainment sets

Abstract: This study explored the ways in which schools addressed the needs of pupils in low-attainment class groups, or sets, in the context of multiple and contrary government policy directives and inconclusive research findings about setting. In this article we have focused on school and classroom practices as well as the organisational processes through which low-attaining pupils were identified, grouped and reviewed within schools. The empirical data reported here predominantly refer to case studies involving class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 22 publications
(34 reference statements)
1
53
0
Order By: Relevance
“…In fact while Dunne et al (2007) found prior attainment was the main predictor of set placement, they found it a relatively poor predictor, with for example over half the pupils with low prior attainment in English being placed in middle or high sets. They also found that social class is a significant predictor of set placement, with those pupils from higher socio-economic status (SES) backgrounds being more likely to be assigned to higher sets, and less likely to be assigned to lower sets.…”
Section: Misallocation To Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact while Dunne et al (2007) found prior attainment was the main predictor of set placement, they found it a relatively poor predictor, with for example over half the pupils with low prior attainment in English being placed in middle or high sets. They also found that social class is a significant predictor of set placement, with those pupils from higher socio-economic status (SES) backgrounds being more likely to be assigned to higher sets, and less likely to be assigned to lower sets.…”
Section: Misallocation To Groupsmentioning
confidence: 99%
“…There is extensive evidence that certain groups of children (those from lower socio-economic groups, and from particular minority ethnic groups) are over-represented in low sets and streams, and that such allocation does not always match 'ability' as designated by IQ tests (Jackson, 1964) or test scores (Dunne et al, 2007). In fact while Dunne et al (2007) found prior attainment was the main predictor of set placement, they found it a relatively poor predictor, with for example over half the pupils with low prior attainment in English being placed in middle or high sets.…”
Section: Misallocation To Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…However additional information may also be used. For example, perceptions of behaviour or interstudent relationships may be used, or students with specific additional needs placed together in order to share the support of a teaching assistant (Dunne et al 2011;Hallam & Ireson 2007). …”
Section: Grouping By 'Ability' and Mixed Attainment Teachingmentioning
confidence: 99%